Central corneal thickness: Important considerate in ophthalmic clinic - Sneha Thakur; Ajay Kumar Saxena; Archna Bhatnagar (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study was to evaluate the relationship of central corneal thickness (CCT) with age, sex, refractive status, and keratometry (KM). Materials and Methods: In our cross-sectional study, 1000 eyes of 500 patients from the outpatient department were randomly selected between July 2014 and December 2015. CCT was measured with a Humphrey ultrasonic pachymeter. Horizontal and vertical curvatures of the cornea were measured with a Bausch and Lomb keratometer, and its mean was calculated. Refractive state was measured with a Priestley-Smith retinoscope and converted to spherical equivalent (SE). The patients were divided into three age groups (Group A [16-30 years], Group B [31-45 years], and Group C [46-60 years]), and the data were analyzed statistically by the Statistical Package for the Social Sciences programme. Results: The mean SE, KM, and CCT of the patients under the study were(-) 0.47 ± 2.26, 43.79 ± 1.18D, and 528.41 ± 19.1 μm. The mean CCT was higher in age Group C (46-60 years) than other groups (P = 0.008), but we found that an increase in age has no impact on CCT after regression analysis. CCT was not affected by sex (p = 0.168). The mean CCT for myopic patients was 522.87 ± 18.03 μm, which was less compared to 536.39 ± 17.753 μm in hypermetropic patients (p ≤ 0.001). Positive correlation was found between CCT and SE (r = 0.520,P≤ 0.001). KM showed negative correlation with CCT (r = −0.288,p≤ 0.001). Conclusion: From our study, we concluded that CCT was related to age, refractive status, and KM, but not to sex.